Association of programmed death ligand‐1 (PD‐L1) expression with treatment outcomes in patients with BRAF mutation‐positive melanoma treated with vemurafenib or cobimetinib combined with vemurafenib. (10th December 2017) - Wongchenko, Matthew J.; Ribas, Antoni; Dréno, Brigitte; Ascierto, Paolo A.; McArthur, Grant A.; Gallo, Jorge D.; Rooney, Isabelle A.; Hsu, Jessie; Koeppen, Hartmut; Yan, Yibing; Larkin, James
Summary: The prognostic significance of programmed death ligand‐1 (PD‐L1) on treatment outcomes in patients receiving BRAF with or without MEK inhibitors is not well understood. This retrospective exploratory analysis evaluated the association of tumour PD‐L1 expression with progression‐free survival (PFS) and overall survival (OS) among 210 patients in the coBRIM trial treated with cobimetinib plus vemurafenib or placebo plus vemurafenib. In the vemurafenib cohort, there was a trend of increased PFS and OS in those with PD‐L1 + melanoma, with hazard ratios (HRs; PD‐L1 + vs. PD‐L1 − ) of 0.70 (95% CI, 0.46–1.07) and 0.69 (95% CI, 0.42–1.13) for PFS and OS, respectively. However, in patients treated with cobimetinib plus vemurafenib, a similar trend was not observed with HRs (PD‐L1 + versus PD‐L1 − ) of 1.04 (95% CI, 0.66–1.68) and 0.94 (95% CI, 0.57–1.57) for PFS and OS, respectively. The combination cobimetinib plus vemurafenib appears to overcome the poor prognosis associated with low PD‐L1 expression.